Pengetahuan Pedagogi Mahasiswa Calon Guru dalam Perencanaan Pengajaran Matematika dan Hubungannya dengan Keyakinan - Muhtarom, Muhtarom (Jurnal Elemen, 2020)
The purpose of this research is to describe the pedagogical knowledge of prospective teachers in designing mathematics learning and its relationship with beliefs about teaching. This research participant was a prospective teacher who was a constructivist belief that had taken a micro-teaching course and had excellent communication skills, as demonstrated by the fluency in delivering ideas. Data is collected through semi-structured interview techniques. The data obtained were coded, simplified, presented, triangulated time for the credibility data, and concluded. The results show that prospective teachers knew in preparing lesson plans and learning media by the curriculum to facilitate students learning in class. The selection of verbal representations, symbol representations, and the selection of contextual problems is in line with his belief that the teacher's role is to guide students and help them discover mathematical concepts actively. Prospective teachers have good knowledge about choosing the right time to ask questions to students. Prospective teachers know when to ask questions, when to reflect on students' answers, and when to ask new questions or give new assignments. Prospective teachers know assessment techniques, namely the assessment of learning outcomes obtained from the way students find solutions to problems and the suitability of problems with solutions made by students.